Development of Learning Media for Kebhinekaan Quartet Cards to Improve Learning Outcomes of Pancasila Education - Dwi Mulyati; Susilo Tri Widodo (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to develop learning media kebhinekaan quartet cards to improve the learning outcomes of grade V elementary school students in the subject of Pancasila education material on cultural diversity. This research uses the Research and Development (R&D) method with a model according to Borg and Gall through 8 of the 10 stages of research. The data collection techniques used in this study are test techniques and non-test techniques. The test technique consists of pretest and posttest, while the non-test technique consists of interviews, documentation, observation, and questionnaires. The data analysis techniques used in this research are initial data analysis and final data analysis. Initial data analysis used a normality test, while final data analysis used a mean difference test (T-Test) and a mean increase test (N-Gain). The results of this study indicate that the media kebhinekaan quartet cards meet the criteria of very feasible with a percentage of 91.25% from media experts and 91.17% from material experts. In the paired sample t-test test, the result is 0.000 <0.005, which means that there is an effect of using the learning media kebhinekaan quartet card. The N-Gain test obtained a score of 0.5212 which is included in the medium category. So it can be concluded that the media kebhinekaan quartet card is feasible and effective to use to improve the learning outcomes of grade V elementary school students in the subject of Pancasila education on cultural diversity material.